Social enrichment mitigates facial expressions and physiological indicators of short-term stress in horses - Ana Caroline Bini de Lima; Vanessa Cristini Sebastião da Fé; Maria Simara Palermo Hernandes; Emily Caroline Pfeifer de Cristo; Ana Gabrieli dos Santos Fagundes Euzébio; Maria Vitória e Silva Sousa; Fabiana Ribeiro Caldara; Viviane Maria Oliveira dos Santos (PLoS ONE, 2026)
This study aimed to evaluate the ability of social noncontact environmental enrichment to facilitate social buffering and to characterize the emotional experience of horses subjected to restraint in stock by assessing physiological parameters and facial expressions. Pantaneiro horses (n = 11) were evaluated in a crossover design with two treatments: social noncontact enrichment during stock restraint and social isolation during stock restraint. Physiological parameters (heart rate, heart rate variability, respiratory rate, ocular temperature by infrared thermography, and auricular temperature by infrared thermometer) and facial expressions (EquiFACS) were assessed throughout the 24-minute restraint period. When horses were accompanied by a conspecific, heart rate, respiratory rate, and eye temperature were lower (p < 0.05) than when they were socially isolated. The frequency of facial expressions associated with stress responses, such as nostril dilator (AD38), inner brow raiser (AU101), upper eyelid raiser (AU5), eye white increase (AD1), ears forward (EAD101), and ears back (EAD104), was also lower (p < 0.05) in social noncontact enrichment compared to social isolation. The combined assessment of facial expressions and physiological parameters provides robust evidence that, during this intervention, the animals experience an emotional state characterized by high arousal and negative valence. In this context, social noncontact environmental enrichment can facilitate social buffering, leading to a reduction in stress indicators associated with high arousal and negative valence.